KONSEPSI INDUSTRIALISASI MADURA BERBASIS SUMBER DAYA LOKAL - Kurniati Indahsari (Karsa: Journal of Social and Islamic Culture)
Abstrac This article explores a concept of Local Based Industrialization in Madura. Industrialization is focused on community development rather than economic development. Three characters of Local Based Industrialization in Madura are: (1) pushing balanced transformation of economic structure; (2) focusing on community development and implementing sustainable development; and (3) developing local resources based industries. By implementing this concept, Madurese can develop without deleting their Islamic and traditional values and characters. Kata-kata kunci industrialisasi Madura, kompetensi inti industri daerah, berbasis sumberdaya lokal, community development